The Effect of Capital Adequacy and Liquidity on Profitability in Food and Beverage Sub Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (ISE) Period 2015-2018 - Irma Melani; Suroso Suroso; Nurul Musqori (Ilomata International Journal of Management, 2019)
This study aims to analyze the effect of the independent variables on the dependent variable. The independent variables are Capital Adequacy (CAR) and Liquidity (CR) while the dependent variable is Profitability (ROA) in Food and Beverage Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange (ISE) for the period of 2015-2018. The sample in this study consisted of 8 companies listed on the Indonesia Stock Exchange (ISE) for 4 years in the 2015-2018 period. The data used in this study is to use the company's financial statement data published on the Indonesia Stock Exchange (ISE) website and the official website of each company. The data used are secondary data and the method used is panel data regression analysis with the help of the Eviews 9 program to obtain a comprehensive picture of the relationship between one variable with another variable. The results showed that CAR significantly influenced ROA, CR did not influence significantly ROA, CAR and CR simultaneously had an effect on ROA. The effect of CAR and CR on ROA of 92.47% while the remaining 7.33% is influenced by other factors not included in the research model.